New Positioning Technique for Harvesting the Sural Nerve in Obese Patients - Bassam M. Addas (Journal of King Abdulaziz University: Medical Sciences, 2023)
The author is describing a new simple technique in positioning the leg while harvesting the sural nerve in obese patients in the supine position. The positioning technique is simple, and all of the required pieces are readily available in most of the operating theaters. The author has used this technique in harvesting thirty nerves with ease and without complications. The main advantage of this technique is saving time and manpower while harvesting the sural nerve, as only one surgeon is required to harvest the nerve with no assistance needed.